Kepastian Hukum Sistem Peradilan Pidana Koneksitas Pasca Putusan Mahkamah Konstitusi Nomor 87/PUU-XXI/2023 - Apriliyanto, Teguh; Putra, Irman; Maryani, Ani (Wajah Hukum, 2025)
The Indonesian criminal justice system faces various legal and practical challenges related to the uncertainty of the forum and coordination mechanisms between the general and military courts. Constitutional Court Decision No. 87/PUU-XXI/2023, read on November 29, 2024, established a new normative basis by integrating the Corruption Eradication Commission (KPK) into the Permanent Connectivity Team, allowing investigations and prosecutions of joint cases to take place in a single process. This study aims to analyze the extent to which this decision strengthens legal certainty in the connected justice system and identify implementation obstacles in the field. The method used is a normative legal approach with a statute approach, a conceptual approach, and a case law approach, supported by a critical review of the effectiveness of the Joint Decree (SKB) establishing the connection team, Standard Operating Procedures (SOPs), and the harmonization of the roles of the Military Prosecutor, Military Police, and the KPK. The results of the study highlight the legal uncertainty in the practice of connectivity between the military and general courts. Constitutional Court Decision No. Regulation No. 87/PUU-XXI/2023 provides a crucial foundation for integrating the Corruption Eradication Commission (KPK) into the Connection Team, enabling integrated case handling. However, its effectiveness remains hampered by technical regulations, inter-agency coordination, and the need for standard operating procedure (SOP) harmonization.